MATHEMATICAL MODELLING OF TECTONIC FACIES ON THE BASIS OF ACOUSTIC ANALYSIS OF METAMORPHIC ROCKS OF KRYVBAS - Безродний, Д. (Київський національний університет імені Тараса Шевченка, 2008)
Design of tectonic facies of the carried out for the models "ferrous quartzite", "slate of biotitoviy" and "quarzite of biotitoviy", with the investigation of the acoustic and resilient properties of metamorphic breeds by cleavage.

Моделювання тектонофацій мезозони здійснено для моделей "залізистий кварцит", "сланець біотитовий" і "кварцит біотитовий", при якому досліджено акустичні і пружні властивості метаморфічних порід при кліважуванні.
МАТЕМАТИЧНЕ МОДЕЛЮВАННЯ ТЕКТОНОФАЦІЙ МЕЗОЗОНИ НА ОСНОВІ АКУСТИЧНОГО АНАЛІЗУ МЕТАМОРФІЧНИХ ПОРІД КРИВБАСУ